Electrochemical Behavior and Determination of Phenylephrine at Silicate Nanotubes Modified Electrode. Issue 9 (16th May 2013) - Qu, Song; Pei, Supeng; Zhang, Shuping
Abstract A novel Silicate nanotubes (SNTs) modified glass carbon (GC) electrode was prepared and used to study the electrochemcial behavior of phenylephrine (PHE) and determine it. The enhanced electrochemical response of PHE at SNTs modified electrode was observed as compared with bare GC electrode. This proposed method displayed a broad linear range and a lower detection limit for PHE. The linear range was from 8 × 10−8 M to 2 × 10−5 M with the detection limit of 1 × 10−8 M. The electrode could be easily regenerated and exhibited high stability and good selectivity. This method was successfully applied to the determination of PHE in drug samples with satisfactory result. The strategy presented here opens a new way for the development of nanoelectronic devices or electrochemical sensors based on SNTs.